2011
DOI: 10.1002/pmic.201000407
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of human embryonic stem cells

Abstract: Human embryonic stem cells (hESCs) offer exciting potential in regenerative medicine for the treatment of a host of diseases including cancer, Alzheimer's and Parkinson's disease. They also provide insight into human development and disease and can be used as models for drug discovery and toxicity analyses. The key properties of hESCs that make them so promising for medical use are that they have the ability to self-renew indefinitely in culture and they are pluripotent, which means that they can differentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 129 publications
1
13
0
Order By: Relevance
“…Membrane proteomic analyses also suggest that BAP31 may be expressed on the surface of hESCs and human embryonal carcinoma cells . Based on the above membrane proteome analyses, it was suggested that BAP31 is likely to be a possible cell surface marker for undifferentiated hESCs . In this study, we demonstrate for the first time that BAP31 is a novel cell surface marker for undifferentiated hESCs.…”
Section: Discussionsupporting
confidence: 52%
“…Membrane proteomic analyses also suggest that BAP31 may be expressed on the surface of hESCs and human embryonal carcinoma cells . Based on the above membrane proteome analyses, it was suggested that BAP31 is likely to be a possible cell surface marker for undifferentiated hESCs . In this study, we demonstrate for the first time that BAP31 is a novel cell surface marker for undifferentiated hESCs.…”
Section: Discussionsupporting
confidence: 52%
“…Given that the basement membrane is the first extracellular matrix (ECM) produced in the developing embryo, it was quickly identified as an important factor for modulating stem cell behavior [23], that plays multiple roles in the stem cell niche. It is perhaps not surprising then that BME is the gold standard for the maintenance of a wide array of human embryonic stem cell (hESC) lines, as it contains all of the proteins that have been shown to promote hESC growth when used individually [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, many researchers investigated the role of EVs released by iPSCs in tissue regeneration. Several proteomic analyses have identified cytokines, chaperones, signaling molecules, plasma membrane proteins, isolated from human pluripotent stem cells [194,195], and it is reasonable to hypothesize that iPSC-EVs contain many kinds of these proteins. Therefore, many researchers shifted their attention to the EVs released by transplanted cells.…”
Section: Induced Pluripotent Stem Cell Derived Evs In Regenerative Mementioning
confidence: 99%